A composite of carbon nanofiber/copper particle-anchored thiol-incorporated silica nanoparticles utilizable for heavy metal adsorption. (October 2022) - Lee, Hoik; Murai, Masaaki; Son, Dongwan; Oh, Seong-Geun; Kim, Myungwoong; Paeng, Keewook; Kim, Ick Soo
Abstract: We report a design and synthesis of a composite comprised of carbon nanofiber (CNF) and Cu particles which thiol-incorporated silica particles are surface-bound. The CNFs bearing homogeneously distributed Cu particles were fabricated via electrospinning of Cu 2+ /polymer solution and subsequent pyrolysis for carbonization. Thiol-incorporated silica nanoparticles (T-Sil) were synthesized via a modified Stöber method and attached to the surface of Cu particles by a simple immersion process to result in T-Sil anchored Cu particle-embedded CNF (T-Sil/Cu–CNF). The morphology of the resulting composite and the formation of Cu particles in the CNF were thoroughly examined and further utilized as an adsorbent material for heavy metal ions of Ni 2+ and Cu 2+ in water. The chemical route not only opened the potential of CNF-based composite materials for water remediation applications, but also provided the possibility for CNF material functionalization without structural damage which is beneficial toward expanding its applicability in complex composite materials. Graphical abstract: Image 1 Highlights: A novel incorporation strategy of functional particles in CNFs is presented. Cu particles are homogeneously distributed and well-embedded in the CNFs. T-Sil particle forms a chemical interaction with the Cu surface of Cu–CNF. T-Sil/Cu–CNF is utilized as an adsorbent materials for heavy metal ion in water. Adsorption kinetic behaviors were evaluated for Cu 2+ and Ni 2+ .